Equivalent circuit method for static and dynamic analysis of magnetoelectric laminated composites - Dong, ShuXiang; Zhai, JunYi (Chinese science bulletin, 2008)
Magnetoelectric equivalent circuit analytical method is presented for laminate composites of magnetostrictive Terfenol-D （TbxDy1-xFe2） and piezoelectric Pb（Zr1-xTix）O3 （PZT） operated in longitudinal magnetized and transverse polarized （or L-T）, and transverse magnetized and transverse polarized （or T-T） modes. Magnetoelectric （ME） couplings both at low-frequency and resonance-frequency have been studied, and our analysis predicts that （i） the ME voltage coefficients of both L-T and T-T modes increase with increasing the thickness of the piezoelectric phase whereas magnetostrictive phase thickness keeps constant, and then tend to saturation when the thickness ratio of piezoelectric phase to magnetic phases is 〉3; （ii） there are the optimum thickness ratios that maximize magnetoelectric （ME） voltage coefficients for the two modes, which are dependent on elastic compliances ratio of piezoelectric phase and magnetostrictive phase; and （iii） the ME voltage coefficients are dramatically increased by a factor of -Qm, when operated at resonance frequency. A series of TerfenoI-D/PZT laminates were fabricated, and the results were compared with the theoretical ones. Experiments confirmed that equivalent circuit method is a useful tool for optimum designs of ME laminates.